2009
DOI: 10.1097/inf.0b013e318199c3b1
|View full text |Cite
|
Sign up to set email alerts
|

Phase-I Study Medi-534, of a Live, Attenuated Intranasal Vaccine Against Respiratory Syncytial Virus and Parainfluenza-3 Virus in Seropositive Children

Abstract: A live, attenuated respiratory syncytial virus and parainfluenza virus type 3 vaccine was evaluated in healthy respiratory syncytial virus/parainfluenza virus type 3 seropositive children aged 1 to 9 years. Three cohorts of 40 children were randomized 1:1 to receive 10, 10, or 10 median tissue culture infectious dose50 MEDI-534 vaccine or placebo. The vaccine's safety profile was similar to placebo, no viral shedding was detected, and the vaccine was minimally immunogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…[30][31][32][33][34] However, several candidate vaccines are in different stages of development for preventing the diseases caused by these viral agents. Candidate vaccines for hRSV and hMPV employ different approaches, including a chimeric virus (hMPV), 35 live attenuated virus (hRSV), 36 and purified proteins (hRSV), 37 among others. Furthermore, recombinant Bacillus Calmette-Gu erin (rBCG) vaccines have been developed using hRSV and hMPV antigens to provide a protective T H 1 response in mice.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] However, several candidate vaccines are in different stages of development for preventing the diseases caused by these viral agents. Candidate vaccines for hRSV and hMPV employ different approaches, including a chimeric virus (hMPV), 35 live attenuated virus (hRSV), 36 and purified proteins (hRSV), 37 among others. Furthermore, recombinant Bacillus Calmette-Gu erin (rBCG) vaccines have been developed using hRSV and hMPV antigens to provide a protective T H 1 response in mice.…”
Section: Introductionmentioning
confidence: 99%
“…This vaccine candidate (MEDI-534) has recently been tested in clinical trials. Although the vaccine was attenuated and safe, it was minimally immunogenic in both adults and children, indicating that further modification may be required [116,117]. However, the major advantage of this approach is that the viral vector is also a vaccine, thus providing protection against multiple pathogens.…”
Section: Live Vectored Rsv Vaccinesmentioning
confidence: 96%
“…RSV lacking SH (rA2DSH) replicated similarly to wild-type (wt) RSV (rA2) in culture but showed a low level of attenuation in the respiratory tracts of rodents and nonhuman primates [77]. Because clinical trials indicated that rA2cpts248/404 Poor (seropositive children) [117] was only slightly underattenuated, the SH gene deletion was incorporated into this vaccine candidate to increase the level of attenuation (Fig. 2b).…”
Section: Rsv Vaccinesmentioning
confidence: 99%
“…More recently, reverse genetics has been used to generate a chimeric BPIV3 virus containing the HPIV3 F and HN envelope genes (12,45) and a chimeric BPIV3 virus containing the HPIV1 and HPIV2 envelope genes (46). A BPIV3/HPIV3 chimeric virus, including an additional RSV G or F gene is immunogenic in rhesus monkeys (47) and does not cause any adverse events in adults and seropositive children, although the vaccine is minimally immunogenic in seropositive individuals (48,49). Recombinant PIV5 expressing a foreign influenza virus HA gene is also under development (50,51).…”
Section: Discussionmentioning
confidence: 99%